KEMISKINAN DI NEGERI KAYA IMAN: DI MANA PERAN ZAKAT DAN WAKAF? - Jailani, Lutfi (Maliki Interdisciplinary Journal, 2025)
Poverty remains a persistent issue in many Muslim-majority countries, particularly in Indonesia, raising critical questions about the effectiveness of the Islamic socio-economic system. Despite the presence of zakat and waqf as key instruments in Islamic teachings to address inequality, their implementation and management continue to face significant challenges. This study aims to examine the structural and managerial obstacles that hinder the optimal role of zakat and waqf in poverty alleviation. Data collection was carried out using a qualitative approach through library research, utilizing secondary data from academic journals, official reports from BAZNAS, the Ministry of Religious Affairs, and other credible publications and online sources. The findings indicate that low public literacy, weak governance, lack of transparency, and poor synergy between government policies and religious institutions are the primary factors impeding the effectiveness of these instruments. The study concludes that policy reform, innovation in waqf asset management, and the integration of zakat into national development strategies are essential to realizing a just and sustainable Islamic economic system.